2011
DOI: 10.1161/strokeaha.110.604249
|View full text |Cite
|
Sign up to set email alerts
|

Using Recombinant Tissue Plasminogen Activator to Treat Acute Ischemic Stroke in China

Abstract: on behalf of the China National Stroke Registry (CNSR) InvestigatorsBackground and Purpose-Little is known about intravenous recombinant tissue plasminogen activator (rtPA) use in China. By accessing the Chinese National Stroke Registry (CNSR), the rate of intravenous rtPA use was reviewed. We specifically examined the issues of prehospital and in-emergency department delay and compared them with the published data from developed countries. Methods-Funded by Chinese government, CNSR is the only nationwide stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
114
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(120 citation statements)
references
References 18 publications
5
114
1
Order By: Relevance
“…However, the proportion of diabetics was higher compared to reports from other countries (15% in the Canadian [13] and Belgian [15] cohorts and 18.8% from China [19]). When comparing Arabs to non-Arabs within our cohort, this proportion was much higher, with 45.2% Arabs reporting diabetes, 77% reporting hypertension and more than 50% reporting dyslipidemia.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…However, the proportion of diabetics was higher compared to reports from other countries (15% in the Canadian [13] and Belgian [15] cohorts and 18.8% from China [19]). When comparing Arabs to non-Arabs within our cohort, this proportion was much higher, with 45.2% Arabs reporting diabetes, 77% reporting hypertension and more than 50% reporting dyslipidemia.…”
Section: Discussioncontrasting
confidence: 67%
“…In-hospital death (%) 12 (6.8) When comparing our results with the initial thrombolysis experience from around the world, several interesting observations can be made. Firstly, the age of stroke onset for our patients is almost two decades younger when compared to Western countries [13][14][15][16], and almost one decade younger then that reported from other Asian countries [17][18][19][20][21]. When Arabs were analyzed separately, the median age of thrombolysed Arab patients was slightly higher (56 years) but still lower than that reported internationally.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…[1][2][3] However, the Japanese drug safety authority has approved the use of alteplase at a dose of 0.6 mg per kilogram after an uncontrolled, open-label study showed that this dose resulted in equivalent clinical outcomes and a lower risk of intracerebral hemorrhage than that reported in published studies in which the 0.9-mg-per-kilogram dose was used. 4 Other registry studies in Asia [5][6][7][8][9][10][11] have shown inconsistent results, but a high risk of symptomatic intracerebral hemorrhage was observed among Asian patients treated with 0.9 mg of alteplase per kilogram in the United States. 12 Differing perceived risks of intracerebral hemorrhage and treatment affordability have led to variations in the doses of intravenous alteplase used to treat patients with acute ischemic stroke in Asia.…”
mentioning
confidence: 99%
“…12 Differing perceived risks of intracerebral hemorrhage and treatment affordability have led to variations in the doses of intravenous alteplase used to treat patients with acute ischemic stroke in Asia. [8][9][10][11] The Enhanced Control of Hypertension and Thrombolysis Stroke Study (ENCHANTED) was designed to compare low-dose with standard-dose intravenous alteplase in patients with acute ischemic stroke. Using a quasi-factorial design, we are also assessing the effects of early intensive lowering of blood pressure as compared with guideline-recommended management in patients with elevated blood pressure; this part of the trial is scheduled to be completed in 2018.…”
mentioning
confidence: 99%